2019
DOI: 10.1002/pld3.131
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time whole‐plant dynamics of heavy metal transport inArabidopsis halleriandArabidopsis thalianaby gamma‐ray imaging

Abstract: Heavy metals such as zinc are essential for plant growth, but toxic at high concentrations. Despite our knowledge of the molecular mechanisms of heavy metal uptake by plants, experimentally addressing the real‐time whole‐plant dynamics of heavy metal uptake and partitioning has remained a challenge. To overcome this, we applied a high sensitivity gamma‐ray imaging system to image uptake and transport of radioactive 65 Zn in whole‐plant assays of Arabidopsis thaliana … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…In agreement, modeling of the Zn supply-dependent spatio-temporal evolution of Zn concentration in root symplast and apoplast of A. thaliana predicted that slight changes in HMA4 transcript levels have a major impact on the radial distribution of Zn in roots and on the root to shoot Zn gradient (Claus et al 2013). This result was recently confirmed in A. halleri using 65 Zn imaging (Kajala et al 2019). It was further shown that a certain extent of functional differentiation exists among the three AhHMA4 copies when expressed in A. thaliana, stemming from differences in expression levels rather than in expression profiles.…”
Section: Root-to-shoot Transfer Of Zinc and Cadmiumsupporting
confidence: 59%
“…In agreement, modeling of the Zn supply-dependent spatio-temporal evolution of Zn concentration in root symplast and apoplast of A. thaliana predicted that slight changes in HMA4 transcript levels have a major impact on the radial distribution of Zn in roots and on the root to shoot Zn gradient (Claus et al 2013). This result was recently confirmed in A. halleri using 65 Zn imaging (Kajala et al 2019). It was further shown that a certain extent of functional differentiation exists among the three AhHMA4 copies when expressed in A. thaliana, stemming from differences in expression levels rather than in expression profiles.…”
Section: Root-to-shoot Transfer Of Zinc and Cadmiumsupporting
confidence: 59%
“…Firstly, modifications to cell wall components and structure favor the retention of metals and provide a mechanical and chemical barrier against their free penetration into the protoplast [ 27 , 28 ]. Similarly, various membrane transporters belonging to the following families: HMAs (heavy metal ATPases, also known as P-type ATPase), NRAMP (natural resistance-associated macrophage protein), CDF (cation diffusion facilitators), YSL (yellow stripe-like), ABC (ATP-binding cassette), COPT (copper transporter), and ZIP (zinc-regulated transporter, iron-regulated transporter-like protein), play an important role in the regulation of toxic ion influx into the protoplast and organelles, and therefore have been extensively discussed in recent research and numerous review articles [ 7 , 29 , 30 , 31 ]. Subsequently, in the cytosol, harmful ions are effectively detoxified and stored in places safe for metabolism in order to prevent deleterious physiological damage.…”
Section: Functional Traits Of Plants Developed In Response To Severe ...mentioning
confidence: 99%
“…The absorption of metals, their translation to different plant tissues, as well as the degree of their tolerance, depend on the metal species, ion bioavailability, plant species and their metabolism (Appenroth, 2010;Kopittke et al, 2010;Xiao et al, 2020). The absorption of metals from soil and their translocation and accumulation among the plants' organs in Arabidopsis thaliana L. (Arabidopsis) have been extensively studied, and the resistance, avoidance, and toxic mechanisms have been elucidated (Kajala et al, 2019;Chen et al, 2020;Simiele et al, 2021). Most studies on the efficiency of metal absorption by Arabidopsis seedlings were focused on soil-to-plant transfer factors, which differ from species to species and are mainly governed by the type of metal absorbed (Schat et al, 2000;Xiao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%